Synthesis and properties of biophenol‐furfural based bioresin for curing of styrene butadiene rubber. Issue 4 (8th February 2023) - Koley, Riya; Chattopadhyay, Santanu; Bhowmick, Anil K.
Abstract: In the present work, biophenol and furfural‐based resol resin was synthesized and utilized for the very first time to cure styrene butadiene rubber (SBR). The reaction was studied over a range of times, temperatures, pH, and furfural to biophenol ratios to fix the optimum conditions. Fourier transform infrared spectroscopy and nuclear magnetic resonance spectroscopy revealed the functional groups and chemical structure of the synthesized resin, respectively. An exothermic peak for the resin curing appeared at 143°C in the differential scanning calorimetry thermogram of the resin. Then, the biophenol‐furfural resin was utilized for the curing of SBR. The synthesized resin increased the tensile strength of the raw rubber from 0.20 ± 0.01 MPa to 1.22 ± 0.10 MPa at 10 phr loading, and the crosslink density was 2.56 × 10 −5  mol/mL. The activation energy for curing SBR containing 10 phr resin was 97 kJ/mol. The storage modulus of the resin‐cured compound was improved. The glass transition temperature of the raw SBR was also shifted from −43.8 to −42.3°C when 10 phr resin was used for the curing. Hence, for the first time, this work reported the utilization of biophenol‐biosourced furfural resin to cure rubbers. Abstract :